Financial deepening and poverty reduction: causality linkage in the case of Malaysia - Mustafa, Siti Aisyah; Zainal, Nur Syuhada; Kassim, Salina (2014)
This paper investigates the interaction between financial deepening and poverty reduction in the case of Malaysia from period of 1975 to 2012. We employed ARDL bounds testing approach to find long run cointegration as well as Granger causality to discover the short run and long run dynamics between the variables. Our findings show that when monetization variable is used a proxy for financial deepening, poverty reduction measured by per capita consumption seems to cause the development of financial sector irrespective of whether the causality test is conducted in the short run or in the long run. The results reflect the importance of aggregate demand on goods and services among households to trigger the size of liquid money in Malaysian economy.